ANALISIS EKONOMI USAHA PETERNAKAN LOVEBIRD (Agapornis) DI KABUPATEN TULUNGAGUNG - Ahsin Daroini; M. Rizqi Rohman Al Habbah (Jurnal Ilmiah Fillia Cendekia, 2017)
The research was conducted in April 2017 at Mrs. Rusna’s Farm in Bendiljati Wetan Village, Sumbergempol Sub District, Tulungagung Regency. The purpose of this study is to determine the feasibility of breeding based on economic evaluation. Primary data and secondary data were obtained by interview and observation method. Descriptive analysis using economic equation formula that is R / C ratio, break even point, margin of safety and rentabilty is used to analyze data. The results show that the cost per year is Rp. 146,908,000 and Rp. 337,462,000 of revenues, from that profit Mrs. Rusna's farm has the right to operate based on R / C ratio (3.3), BEP price Rp. 142,768, BEP production volume 312 tail, MOS (69,7%) and rentability (39,54%).